Positioning Analysis of Automotive Mold & Dies Industry Business Using Multidimensional Scaling Method in PT. Duta Panitra Serco - Oviyan Patra; Yustariliska Vilestina Putri (Kusuma Negara Business School, 2020)
This research is an analysis of the positioning of PT. Duta Panitra Serco by identifying market opportunities in the automotive Mold & Dies manufacturing industry. Companies that become respondents are in areas in Cikarang, Purwakarta, Karawang and Bandung. Determining the potential market by forecasting demand. Importance Factor Analysis uses factor analysis with the help of SPSS software. The results of the factor analysis contained 5 attributes, namely Mold & Dies Quality, Service Quality, Affordable Product Prices, Output Capability, Product & Company Value Added. Positioning Companies using the Multidimensional Scaling Scale (MDS). Based on the results of data processing, it was concluded that PT. Duta Panitra Serco can occupy quadrant 4, which is the quadrant in line with the factors 1,2 & 3 to compete in the market so that they can dominate the existing market. In this market the company will experience a little competition with PT. Wafiq Mitra Teknik because currently PT. Wafiq Teknik Partners have started to enter quadrant 4.